2017
DOI: 10.1038/ng.3970
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of rare inherited and de novo variants in 2,871 congenital heart disease probands

Abstract: Congenital heart disease (CHD) is the leading cause of mortality from birth defects. Exome sequencing of a single cohort of 2,871 CHD probands including 2,645 parent-offspring trios implicated rare inherited mutations in 1.8%, including a recessive founder mutation in GDF1 accounting for ~5% of severe CHD in Ashkenazim, recessive genotypes in MYH6 accounting for ~11% of Shone complex, and dominant FLT4 mutations accounting for 2.3% of Tetralogy of Fallot. De novo mutations (DNMs) accounted for 8% of cases, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

55
1,062
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 714 publications
(1,118 citation statements)
references
References 61 publications
55
1,062
1
Order By: Relevance
“…While more commonly associated with cardiomyopathy (dilated, hypertrophic, or restrictive), mutations in genes encoding for components of the cardiac sarcomere, the basic contractile unit of striated muscle, have been determined to be responsible for familial and sporadic CHD. Examples include mutations in MYH7 (β myosin heavy chain) in individuals with Ebstein anomaly of the tricuspid valve, in ACTC1 (cardiac α actin) in familial ASD, and in MYH6 (α myosin heavy chain 6) in autosomal dominant familial ASD and sporadic cases of more complex CHD, including Shone complex and HLHS . There is mounting evidence that genetic variation in sarcomeric genes can concurrently cause CHD and affect ventricular function.…”
Section: Genetic Architecture Of Chdmentioning
confidence: 99%
See 1 more Smart Citation
“…While more commonly associated with cardiomyopathy (dilated, hypertrophic, or restrictive), mutations in genes encoding for components of the cardiac sarcomere, the basic contractile unit of striated muscle, have been determined to be responsible for familial and sporadic CHD. Examples include mutations in MYH7 (β myosin heavy chain) in individuals with Ebstein anomaly of the tricuspid valve, in ACTC1 (cardiac α actin) in familial ASD, and in MYH6 (α myosin heavy chain 6) in autosomal dominant familial ASD and sporadic cases of more complex CHD, including Shone complex and HLHS . There is mounting evidence that genetic variation in sarcomeric genes can concurrently cause CHD and affect ventricular function.…”
Section: Genetic Architecture Of Chdmentioning
confidence: 99%
“…Similarly, multiple studies have shown that CHD patients with sarcomeric mutations have differential clinical outcomes, including reduced ventricular performance and transplant‐free survival. In a recent study of 2645 parent‐offspring trios and 226 singletons who underwent exome sequencing by the PCGC, 7 had recessive genotypes involving MYH6 . Five of the 7 had left ventricular outflow tract obstructive lesions, including 4 with Shone complex (which is characterized by mitral and aortic valve abnormalities).…”
Section: Genetic Architecture Of Chdmentioning
confidence: 99%
“…Common variant genome-wide association studies (GWAS) have been particularly successful in adult-onset disorders and most loci discovered are in the noncoding genome 7 . In early-onset disorders with reduced fecundity, including autism spectrum disorder (ASD) 8 , discovery has been largely driven by the identification of extremely rare, gene-disrupting, de novo mutations that exert considerable risk 4,5,9 .…”
mentioning
confidence: 99%
“…CHD can be divided into nonsyndromic phenotypes, including gene mutations, and syndromic phenotypes, including chromosomal abnormalities, such as Down's syndrome, Edwards syndrome, and Patau syndrome. Only about one-third of CHD cases have been described as clear genetic or chromosomal abnormality cases [2,3]. The causes of CHD are complex and involve interaction among the environment, genetics, and epigenetics.…”
Section: Introductionmentioning
confidence: 99%